Verified Software: Theories, Tools, Experiments Third International Conference, VSTTE 2010, Edinburgh, UK, August 16-19, 2010. Proceedings - Leavens, Gary T.; OHearn, Peter.; Rajamani, Sriram K. (Lecture Notes in Computer Science,, 2010)
This volume contains the proceedings of the third working conference on Verified Software: Theories, Tools, and Experiments, VSTTE 2010, held in Edinburgh, UK, in August 2010. The 11 papers presented together with 3 invited talks were carefully revised and selected for inclusion in the book. This third conference is part of the Verified Software Initiative (VSI), which is a 15 year international project that focuses on the scientific and technical challenges of producing verified software. The goal of VSTTE 2010 was to advance the state of the art in the science and technology of software verification through the interaction of theory development, tool evolution, and experimental validation. The accepted papers represent work on verification techniques, specification languages, formal calculi, verification tools, solutions to challenge problems, software design methods, reusable components, refinement methodologies, and requirements modeling.